IMPLIKASI UU NO. 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA TERHADAP PERLINDUNGAN HUKUM BANK SEBAGAI KREDITUR - Diah Sulistyani Ratna Sediati (Masalah-Masalah Hukum, 2010)
The existence of the legal regulation no, 42 in 1999 is the first input which is very strategic, since the legal regulation is the product of the reformation or the product of the democrazation which has tried to accommodate comprehensively some aspiration, not only superstructure, infrastructure aspiration (society who need), expertise aspiration but also the global aspiration as it is hoped by the society or the international organization based on the value of the democrazy namely the supremacy of the law. Inthis case, the role of the legal regulation beside as both the mechanism of integration and as the role of the society change (law as a tool of policy or social enginerting) in order to create the certainty of the law and the justice which is difficult to be achieved just by the jurisprudence, as it happens before the legal regulation is legalized. that is why, the legal regulation no. 42 in 1999 also brings the mission on the achievement of the political law like the importance of economy, the certainy and the protection of the law for the parties (goal attainment). On the way, there are a lot of handicaps to implement the legal regulation no. 42 in 199 about the guaranty of the fiducia which is out of maximum in accommodating especially in the field of the credit matter, it is expected to amend the regulation to give the protection of the law for the creditor especially in the field on the credit matter and banking in Indonesia